Avoiding drunk driving: the behaviour of South African general drivers - Karl Peltzer (Acta Academica, 2002)
The aim of this article is to examine the degree to which drivers participate in activities aimed at avoiding drunk-driving victimisation, and to assess protective behaviour in relation to drunk driving. The sample included 100 black and 100 white drivers drawn from the general public of an urban area in the then Northern Province of South Africa. 59% reported having practised three out of four self-protective behaviours and 68% having practised all four other-protective behaviours in the preceding twelve months. Some evidence was found to support the fear-andvictimisation model, since one or more individual factors were related to each of the four self-protective behaviours and three of the four other-protective behaviours. Important gender and racial differences were also found.